2016
DOI: 10.1016/j.wjorl.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of serial physical examinations in the management of angioedema involving the head and neck: A prospective observational study

Abstract: ObjectiveTo elucidate the progression of angioedema of the head and neck with routine management and to assess the utility of serial physical exams and fiberoptic laryngoscopy in its management.MethodsThis study was a prospective observational research. From 2013 to 2014, a prospective observational study was conducted at a tertiary referral center. Forty patient were approached, 7 refused, 33 (18–90 years old) were enrolled. Patients presented with angioedema involving the head and neck over a 12 month period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…3 While this condition can affect any part of the body, it most commonly occurs in the face and perioral region. 4 Currently, angioedema is broadly categorized based upon the presence or absence of an inheritance pattern. 5 Most cases in the United States are acquired angioedema and most commonly associated with angiotensin-converting enzyme inhibitors (ACE-I).…”
Section: Introductionmentioning
confidence: 99%
“…3 While this condition can affect any part of the body, it most commonly occurs in the face and perioral region. 4 Currently, angioedema is broadly categorized based upon the presence or absence of an inheritance pattern. 5 Most cases in the United States are acquired angioedema and most commonly associated with angiotensin-converting enzyme inhibitors (ACE-I).…”
Section: Introductionmentioning
confidence: 99%
“…On exam, the upper lip was the most commonly involved site (58%), followed by the lower lip (45%), anterior tongue (30%), face (21%), soft palate (18%), supraglottis (18%), floor of mouth (15%), base of tongue (12%), and neck (9%). No glottic edema was observed in any of the patients, and more than one site was involved in 76% of patients 4 . Only four patients (12%) went on to require intubation.…”
Section: Literature Reviewmentioning
confidence: 83%
“…No glottic edema was observed in any of the patients, and more than one site was involved in 76% of patients. 4 Only four patients (12%) went on to require intubation. Linkov et al found that no anatomic site had a statistical association with intubation.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Our institution, a large tertiary‐care urban medical center, treats a large volume of patients who present with primary angioedema, and we have previously described our experiences with ACE‐I related angioedema 8‐10 . However, in our clinical practice, we have come to recognize an unexpectedly large group of patients who present with recurrent episodes of angioedema, most of whom fall under the acquired idiopathic primary angioedema category.…”
Section: Introductionmentioning
confidence: 99%